2016
DOI: 10.1039/c6ta01219a
|View full text |Cite|
|
Sign up to set email alerts
|

Polypyrrole multilayer-laminated cellulose for large-scale repeatable mercury ion removal

Abstract: In this research, we report a polypyrrole (PPy) multilayer-laminated cellulose network aimed at the costeffective removal of aqueous potentially toxic metal ions with high adsorption efficiency and good adsorbent recyclability. The preparation of conformal adsorbent coatings on a fibrous cellulose network was accomplished by performing multiple cycles of simple dip-coating of a non-toxic oxidant and vapor-phase polymerization of PPy. The resultant PPy multilayer-deposited cellulose exhibited stable adhesion be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…in either developing or industrialized nations has posed serious environmental and health threats . Particularly, mercury poisoning can cause Minamata disease, which can permanently impair brain functions of children and adults via direct contact or bioaccumulation . It is extremely desirable to remove mercury from aqueous resources effectively and facilely.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…in either developing or industrialized nations has posed serious environmental and health threats . Particularly, mercury poisoning can cause Minamata disease, which can permanently impair brain functions of children and adults via direct contact or bioaccumulation . It is extremely desirable to remove mercury from aqueous resources effectively and facilely.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, conventional solar steamer techniques cannot remove mercury effectively, since the contaminant volatilizes along with the water steam. Amidst a variety of other water treatment technologies, chemical adsorption emerges as one of the most potential techniques to remove toxic mercury ions . Owing to the strong soft–soft interactions between mercury and sulfur, sulfur‐containing materials have demonstrated feasibility in mercury removal .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We proposed a simple impregnation technique to polymerize a conjugated polymer (PPy) on a cellulose membrane. (28) First, the membrane was impregnated by dipping it in an aqueous solution of metal salt (FeCl 3 , as an oxidant), which was prepared by dissolving the metal salt in water, with different molar concentrations of oxidant (0.25, 0.5, and 1 M) for 1 h and then exposed to open air to dry under ambient conditions. Subsequently, all metal-salt containing cellulose membranes (deep yellow color) were exposed to pyrrole vapor.…”
Section: Preparation Of Cell-ppy Hybridmentioning
confidence: 99%
“…Research has shown that polypyrrole has potential application in electronic conductors, optical switching devices, sensors, batteries, energy storage devices, supercapacitors, as adsorbents and as catalysts in electronic devices . Furthermore, application of polyrrole in the construction of molecularly imprinted polymers based sensors has been reported in the determination of caffeine , bisphenol A methimazole d‐penicillamine dopamine vitamin c theophylline . These electrochemical sensors displayed good selectivity and excellent electrochemical properties due to the tendency of polypyrrole to interact with analytes via hydrogen bonds and ion exchange systems.…”
Section: Introductionmentioning
confidence: 99%